2015
DOI: 10.1002/adhm.201400670
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation of Drug‐Resistant Cancer Cells Using Molecularly Targeted Carboxyl‐Functionalized Biodegradable Graphene

Abstract: Under ultralow radiofrequency (RF) power, transferrin-conjugated graphene nanoparticles can thermally ablate drug- or radiation-resistant cancer cells very effectively. The results suggest that graphene-based RF hyperthermia can be an efficient method to manage drug-/radiation-resistant cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Graphene and its derivatives have also been explored for radiofrequency-based ablation of cancer cells. Recently, Sasidharan et al reported using carboxylic acid functionalized graphene for in vitro ablation of drug-resistant cancer cells using a radiofrequency electromagnetic radiation source [92]. Carboxylatedgraphene was functionalized with transferrin to target cancer cells and stimulated with a 13.56 MHz radiofrequency power source.…”
Section: Hyperthermia and Photodynamic Therapymentioning
confidence: 99%
“…Graphene and its derivatives have also been explored for radiofrequency-based ablation of cancer cells. Recently, Sasidharan et al reported using carboxylic acid functionalized graphene for in vitro ablation of drug-resistant cancer cells using a radiofrequency electromagnetic radiation source [92]. Carboxylatedgraphene was functionalized with transferrin to target cancer cells and stimulated with a 13.56 MHz radiofrequency power source.…”
Section: Hyperthermia and Photodynamic Therapymentioning
confidence: 99%
“…Sasidharan et al reported that transferrin modified carboxylated graphene would be ideal for targeting and ablating drug and radiation resistant chronic myelogenous leukemic cancer cells using lower RF exposures for 5 min. The study highlighted the potential of graphene as RF responsive biomaterial, which was efficient enough to abolish CML without any chemo agents, making new possibilities for further RFassisted cancer therapy [79]. The RF ablation induced by transferrin conjugated carboxylated graphene was very specific towards clinically relevant K562 cells (Fig.…”
Section: Transferrin Functionalized Graphene For Radiation/drug Resismentioning
confidence: 83%
“…11) as confirmed by different biological assays, throwing light on their possibilities towards new cancer treatment regimens along with RFA. Even though the exact mechanism for RFA using transferrin conjugated graphene is not mentioned, these are reported to be better hyperthermic agents compared to Au-NPs and SWNTs [79]. Since transferrin receptors are overexpressed in brain tumors such as glioma, it would be a great approach to target glioma cells using transferrin conjugated graphene, along with RF treatment.…”
Section: Transferrin Functionalized Graphene For Radiation/drug Resismentioning
confidence: 99%
“…NIR‐based PTT is marred by several drawbacks including low tissue penetration (1–5 cm) and safety concerns associated with high‐energy laser exposure . A shortwave radiofrequency (RF) field in MHz range offers relatively long (∼30 cm) and even total‐body‐penetrating RF energy delivery with minimal toxicity . However, the invasive nature of RFA has limited usage for clinical applications.…”
Section: Aunm As Therapeuticsmentioning
confidence: 99%